2015
DOI: 10.1002/2014jd022984
|View full text |Cite
|
Sign up to set email alerts
|

Toronto area ozone: Long‐term measurements and modeled sources of poor air quality events

Abstract: The University of Toronto Atmospheric Observatory and Environment Canada's Centre for Atmospheric Research Experiments each has over a decade of ground-based Fourier transform infrared (FTIR) spectroscopy measurements in southern Ontario. We present the Toronto area FTIR time series from 2002 to 2013 of two tropospheric trace gases-ozone and carbon monoxide-along with surface in situ measurements taken by government monitoring programs. We interpret their variability with the GEOS-Chem chemical transport model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Measurements are made in the midinfrared at a resolution of 0.0035 cm −1 using a KBr beam splitter and either an InSb or HgCdTe detector and a series of optical filters. A detailed description of the Bomem DA8 at TAO is given by Wiacek et al [] and Whaley et al []. Measurements are made with the same optical components and resolution as the PEARL instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements are made in the midinfrared at a resolution of 0.0035 cm −1 using a KBr beam splitter and either an InSb or HgCdTe detector and a series of optical filters. A detailed description of the Bomem DA8 at TAO is given by Wiacek et al [] and Whaley et al []. Measurements are made with the same optical components and resolution as the PEARL instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Toronto, an urban site, is most sensitive to local pollution sources in southeast Canada and the United States (Whaley et al, 2015) and periodically subject to wildfire pollution episodes as demonstrated by Griffin et al (2013); Whaley et al (2015).…”
Section: Mid-latitude Sitesmentioning
confidence: 99%
“…where regular solar measurements began in 2002. In contrast to most NDACC stations, the Toronto station is highly affected by the densely populated areas of the city of Toronto itself (the centre of Canada's largest population) and the cities and industrial centres of the north-eastern United States, enabling measurements of tropospheric pollutants (Whaley et al, 2015). In addition, the station's location makes it well suited for measurements of midlatitude stratospheric ozone, related species, and greenhouse gases (Wiacek et al, 2007).…”
Section: Observation Sitesmentioning
confidence: 99%